2018
DOI: 10.5222/ankem.2018.1820
|View full text |Cite
|
Sign up to set email alerts
|

Which Antibiotics Should be First Line Options for Empirical Treatment of Urinary Tract Infections During Pregnancy?

Abstract: Üriner sistem infeksiyonu gebelikte sık görülen bir sağlık sorunudur. Ancak, gebelikte güvenle kullanılabilen antibiyotikler fetal toksisite riski nedeniyle kısıtlıdır. Bu çalışmada gebe kadınların idrar kültürlerinden izole edilen patojenlerin antimikrobiyal direnç profillerinin belirlenmesi ve ampirik tedavide tercih edilebilecek antibiyotiklerin tespiti amaçlanmıştır. Ocak 2015-Ocak 2016 tarihleri arasında Karabük Eğitim ve Araştırma Hastanesi'ne başvuran gebelerin idrar örneklerinden izole edilen bakterile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 19 publications
(51 reference statements)
1
9
0
Order By: Relevance
“…In the present study, among 1710 urine samples cultured from asymptomatic pregnant women, 123 samples yielded uropathogens, showing a prevalence of 7.2%. This is consistent with the prevalence of ABU seen in other studies by Aktun et al ( 2), Tokak et al ( 5), and Aşgın et al (6), respectively, 7.1%, 7.8%, and 10%. The occurrence of significant bacteria in the lower urinary tract with no symptoms makes the condition more susceptible in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, among 1710 urine samples cultured from asymptomatic pregnant women, 123 samples yielded uropathogens, showing a prevalence of 7.2%. This is consistent with the prevalence of ABU seen in other studies by Aktun et al ( 2), Tokak et al ( 5), and Aşgın et al (6), respectively, 7.1%, 7.8%, and 10%. The occurrence of significant bacteria in the lower urinary tract with no symptoms makes the condition more susceptible in pregnant women.…”
Section: Discussionsupporting
confidence: 92%
“…These factors lead to urinary stasis, dysfunctional urethral valves, and vesicoureteral reflux that assists bacterial colonization (16). Several studies have reported that the geographic variability of pathogens in the case of ABU is limited with the predominance of gram-negative, particularly E. coli (2,5,6,17,18). We also detected gram-negative isolates as the causative agent at a higher rate, 67.5%.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The increase in uterine dimensions with pregnancy, facilitates urinary tract infections by causing stasis in the dilatation of urinary flow in the ureter and bladder with the effect of progesterone. Glucosuria, urine osmolality and changes in urine pH during pregnancy are also factors that predispose to urinary tract infections (2,3).…”
Section: Introductionmentioning
confidence: 99%